THE DEPICTION OF VILLAGE LIFE AND THEIR PROBLEMS IN ‘GODAN’ BY PREMCHAND AND ‘GAMPERALIYA’ BY A SRI LANKAN NOVELIST MARTIN WIKRAMASINGHA - Rajapaksha, RKD NilanthiKumari (International Journal of Research -GRANTHAALAYAH, 2017)
Godan was written in India in1936 by Premchand.Gamperaliya was written in Sri Lanka in 1944 by Martin Wickramasinghe. Both the writers are from different countries, yet many similarities are found in their Novels. Being contemporaries has immediate effect on the content of both Writers. The purpose of this study was to find those similarities. After study of both novels, often many similarities could be found such as blind beliefs, poverty and the habits of the rural population.